2021
DOI: 10.2147/rmhp.s330282
|View full text |Cite
|
Sign up to set email alerts
|

Suicidality in Bangladeshi Young Adults During the COVID-19 Pandemic: The Role of Behavioral Factors, COVID-19 Risk and Fear, and Mental Health Problems

Abstract: Background It is said that psychological stressors have risen during the COVID-19 pandemic, which may contribute to suicidality. A few studies were conducted investigating suicidality amid the first wave of the pandemic in Bangladesh, but none of these studies explored the predictive role of the suicidality-related factors (eg, behavior and health-related variables, COVID-19 risk, fear of COVID-19). Thus, this study aimed to investigate the prevalence of suicidality and the predictive models expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 49 publications
(85 reference statements)
1
23
1
Order By: Relevance
“…This increased prevalence of psychiatric symptoms in females could be because they correspond to a greater percentage in different sectors of workers and employees that could be impacted negatively due to the COVID-19 pandemic; for example, in health-care industries or as in retail sectors. Besides, females prevalently suffer from mental health problems, which has also been reported in the systematic review of studies during the COVID-19 pandemic, for instance, reported from Bangladesh (al Mamun et al, 2021) and China, Spain, Italy, Iran, USA, Turkey, Nepal, and Denmark (Xiong et al, 2020).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…This increased prevalence of psychiatric symptoms in females could be because they correspond to a greater percentage in different sectors of workers and employees that could be impacted negatively due to the COVID-19 pandemic; for example, in health-care industries or as in retail sectors. Besides, females prevalently suffer from mental health problems, which has also been reported in the systematic review of studies during the COVID-19 pandemic, for instance, reported from Bangladesh (al Mamun et al, 2021) and China, Spain, Italy, Iran, USA, Turkey, Nepal, and Denmark (Xiong et al, 2020).…”
Section: Discussionmentioning
confidence: 60%
“…Due to the fear of COVID-19 contamination, the pandemic has significantly changed daily lives because of restricted movements to slow down the virus spread. Along with this, people are experiencing new realities such as working from home, attending online schooling, lack of face-to-face contact with friends and family members, and rising unemployment, which are the probable factors of mental illness (al Mamun et al, 2021;Hosen et al, 2021). Furthermore, compared to the prevalence of psychiatric symptoms before the pandemic, significantly higher levels of their rates have been observed across the world (Hosen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After more than a year since the emergence of SARS-CoV-2, it has now spread to nearly 200 countries around the globe with a staggering number of 120 million confirmed cases and 2.6 million deaths [ 1 , 2 ]. It has brought the world to its knees, imposing lockdowns, closure of academic institutions, inciting adverse psychological impacts, adopting the e-learning education system and work from home policy [ 3 5 ]. The world is relentlessly searching for new strategies to cope with the ‘new normal’ and resume daily work and business.…”
Section: Introductionmentioning
confidence: 99%